2003
DOI: 10.1002/jmv.10346
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of endemic Norwalk‐like virus‐associated gastroenteritis

Abstract: Endemic gastroenteritis associated with the Norwalk-like viruses (NLVs) is little understood. This study tested for NLV in gastroenteritis cases in 257 households in Melbourne, Australia, for the period September 1997 to February 1999 by a reverse transcription hemi-nested polymerase chain reaction. Positive samples were studied by nucleotide sequencing and phylogenetic analysis. NLV was detected in 73 (11.4%) of 638 faecal specimens tested. Twelve (1.9%) were NLV genogroup 1 (G1) and 61 (9.6%) NLV genogroup 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
3
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 39 publications
3
60
3
1
Order By: Relevance
“…Most of the studies on seasonality describe winter peaks in NoV-associated outbreaks or sporadic cases (Fankhauser et al 1998, Fretz 2005 and some reports, in spring and summer, varying according to the NoV genogroups (Marshall et al 2003). Prevalence of NoV at the beginning of the dry season was previously observed in Vietnam (Hansman et al 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most of the studies on seasonality describe winter peaks in NoV-associated outbreaks or sporadic cases (Fankhauser et al 1998, Fretz 2005 and some reports, in spring and summer, varying according to the NoV genogroups (Marshall et al 2003). Prevalence of NoV at the beginning of the dry season was previously observed in Vietnam (Hansman et al 2004).…”
Section: Discussionmentioning
confidence: 93%
“…NoVs are the major cause of epidemic gastroenteritis worldwide and are related to the consumption of food and water or aquatic recreational activities attacking persons of all ages (de Wit et al 2003), as well as outbreaks in nurseries, hospitals, daycare centers and hotels (Gallimore et al 2004, de Wit et al 2007). However, since the 1990s, molecular procedures have recognized this virus as a common agent of sporadic self-limiting gastroenteritis (de Wit et al 2001, Marshall et al 2003, Oh et al 2003.…”
mentioning
confidence: 99%
“…In this study, multiple norovirus GII sequences were detected in the same outbreak, but norovirus GI and GII sequences were not detected in the same outbreak. The low infectious dose (22) and prolonged shedding (11) of norovirus makes transmission almost certain, although we could not be certain whether foods were contaminated. Mean viral loads of GI and GII were found to be 2.79 ϫ 10 7 and 3.81 ϫ 10 8 copies/g of stool, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Norovirus is the most common cause of infectious intestinal disease (IID) in the community in highincome countries [1][2][3][4]. Norovirus infection has also been identified in a substantial proportion of individuals with no IID symptoms in several community-based studies, with prevelances of up to 16 % reported in high-income countries [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%